Are Sexist Attitudes and Gender Stereotypes Linked? A Critical Feminist Approach With a Spanish Sample - García-Sánchez, Rubén; Almendros, Carmen; Aramayona, Begoña; Martín, María Jesús; Soria-Oliver, María; López, Jorge S.; Martínez, José Manuel (Frontiers in Psychology, 2019)
The present study aims to verify the psychometric properties of the Spanish versions of the Social Roles Questionnaire (SRQ; Baber & Tucker, 2006), Modern Sexism scale (MS) and Old-fashioned Sexism scale (OFS; Swim et al. Swim & Cohen, 1997). Enough support was found to maintain the original factor structure of all instruments in their Spanish version. Differences between men and women in the scores are commented on, mainly because certain sexist attitudes have been overcome with greater success in the current Spanish society, while other issues, such as distribution of power in organizational hierarchies or distribution of tasks in the household, where traditional unequal positions are still maintained. In all cases, it was found that men showed greater support for sexist attitudes. The correlations between the three instruments were as expected in assessing sexist attitudes that tend to relate to each other. Eventually, we found no empirical evidence for the postulated link between sexist attitudes and traditional gender stereotypes. Our results call for the validity and effectiveness of the classic theories of gender psychology, such as gender schema theories (Well, 1981; Markus et al., 1982) and the notion of a gender belief system (Deaux & Kite, 1987; 2001).